Does the minimum wage cause inefficient rationing? - Luttmer, Erzo F. P. (Working paper series / National Bureau of Economic Research, 2007)
This paper investigates whether the minimum wage leads to inefficient job rationing. By not allowing wages to clear the labor market, the minimum wage could cause workers with low reservation wages to be rationed out while equally skilled workers with higher reservation wages are employed. This paper exploits the overlapping nature of the CPS panels to more precisely identify those most affected by the minimum wage, a group I refer to as the "unskilled." I test for inefficient rationing by examining whether the reservation wages of employed unskilled workers in states where the 1990-1991 federal minimum wage increase had the largest impact rose relative to reservation wages of unskilled workers in other states. I find that reservation wages of unskilled workers in high-impact states did not rise relative to reservation wages in other states, indicating that the increase in the minimum wage did not cause jobs to be allocated less efficiently.